Study of Various Reactive Fault Tolerance Techniques in Cloud Computing - Kumar, Atul; Malhotra, Deepti (International Journal of Computer Sciences and Engineering, 2025)
Cloud is large, complex and distributed in nature. It has many features like availability, Reliability and performance of the cloud. Due to its large size and complex nature it is prone to various types of fault and failure like data unavailable, data deletion or corruption etc. Cloud are made as fault tolerant system that tolerate any imminent fault or failure, but still sometime fault happens that disrupts the normal service of cloud. Many researchers gave different technique like replication, checkpointing , Retry ,resubmission etc. to tolerate the failure. In this paper, study of various reactive fault tolerance techniques has been done and after analysis conclusion is presented with some future scope. Keywords: Replication, Checkpointing, Resubmission, Reliability